2015
DOI: 10.1134/s1029959915030054
|View full text |Cite
|
Sign up to set email alerts
|

Young’s modulus and Poisson’s ratio for seven-constant tetragonal crystals and nano/microtubes

Abstract: In the paper, the elasticity theory was applied to consider the mechanical properties of rectilinearly anisotropic seven-constant tetragonal crystals and their cylindrically anisotropic nano/microtubes with and with no chiral angle, being the angle between the crystallographic symmetry axis and elongated tube axis. It is found that the number of crystals with negative Poissons ratio is the least for rectilinear anisotropy and is much larger for curvilinear anisotropy. With a nonzero chiral angle, all nano/micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…An analysis of average Poisson's ratio have shown that all hexagonal crystals have positive Poisson's ratio [9]. We note that more than four hundred crystals with negative Poisson's ratio (auxetics) are detected for crystals of other crystalline systems [5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The least number of auxetics is found among hexagonal crystals, and the largest amount is detected among cubic crystals (more than three hundred).…”
Section: Introductionmentioning
confidence: 72%
“…An analysis of average Poisson's ratio have shown that all hexagonal crystals have positive Poisson's ratio [9]. We note that more than four hundred crystals with negative Poisson's ratio (auxetics) are detected for crystals of other crystalline systems [5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The least number of auxetics is found among hexagonal crystals, and the largest amount is detected among cubic crystals (more than three hundred).…”
Section: Introductionmentioning
confidence: 72%
“…In Voigt's notation for body-centered tetragonal structures, Poisson's ratio for the normal direction n, when the elongation happens along direction l, can be written as [56]:…”
Section: Anisotropy Of Elastic Propertiesmentioning
confidence: 99%
“…Structures considered in the present work belong to different crystal systems. For many anisotropic materials of various crystal systems (cubic, hexagonal, rhombohedral, tetragonal , orthorhombic , monoclinic, and triclinic) negative Poisson's ratio was observed. To date, more than 450 crystals with negative Poisson's ratio (auxetic crystals) were found.…”
Section: Introductionmentioning
confidence: 99%